Spontaneous Self‐Distancing and Adaptive Self‐Reflection Across Adolescence. Issue 4 (15th April 2015) - White, Rachel E.; Kross, Ethan; Duckworth, Angela L.
<x xml:space="preserve">Abstract</x> Experiments performed primarily with adults show that self‐distancing facilitates adaptive self‐reflection. However, no research has investigated whether adolescents spontaneously engage in this process or whether doing so is linked to adaptive outcomes. In this study, 226 African American adolescents, aged 11–20, reflected on an anger‐related interpersonal experience. As expected, spontaneous self‐distancing during reflection predicted lower levels of emotional reactivity by leading adolescents to reconstrue (rather than recount) their experience and blame their partner less. Moreover, the inverse relation between self‐distancing and emotional reactivity strengthened with age. These findings highlight the role that self‐distancing plays in fostering adaptive self‐reflection in adolescence, and begin to elucidate the role that development plays in enhancing the benefits of engaging in this process.